Media and Entrepreneurship, A Revisit with a Decade of Progress: A Bibliometric Analysis of Media Entrepreneurship Research Between 2005 and 2017 - Hang, Min (Nordic Journal of Media Management, 2020)
Purpose: This article is for the purpose of presenting a continued observation on the research of media and entrepreneurship. Media and entrepreneurship have strong relevance to each other—on the one hand, essential characteristics of entrepreneurship including innovation and novel ways of content creation are crucial in building media business success; on the other hand, media play a vital role in promoting an entrepreneurial spirit, by transmitting values and images ascribed to it—this special relationship has been examined a decade ago by an earlier study conducted by this author. Well past the time of media industry development and landscape transformation, much progress has been made since then, it is highly worthwhile to revisit the topic and to identify changes in the field. Therefore, the current article presents a continued study, it aims at observing the status quo of the field of media entrepreneurship research and proposing an agenda for future development. Methodology: The study was conducted by a bibliographic analysis on the scholarly work published between 2005 and 2017. Findings from the study indicate growing interests in the research of media and entrepreneurship. The field of inquiries is getting to be more mature, with the progress made on the fundamental conceptual building. In the existing literature, innovation has been a central topic for study, and entrepreneurial journalism was emerged as a new focal issue; meanwhile, use of social media to promote entrepreneurship has also attracted close academic attention. Findings/Contribution: The study provides practical implications to media entrepreneurs and social implications to promote entrepreneurship spirit through traditional and new media platforms. The article also contributes original value to understanding the intrinsic linkage between media and entrepreneurship.